CircRNA SCAR Improves High-Glucose-Induced Mitochondrial Dysfunction and Permeability Damage in Retinal Microvascular Endothelial Cells - Wu, Rong; Huang, Sheng; Xie, Jin-feng; Wen, Nian-lian; Wen, Min; Zhong, Su-e (Hormone and Metabolic Research, 2023)
This study was designed to assess the role and mechanism of circRNA SCAR in human retinal microvascular endothelial cells (hRMVECs) treated with high glucose. Quantitative real-time polymerase chain reaction (qRT-PCR) and cell counting kit 8 (CCK-8) were used to detect the effects of different concentrations of glucose on circRNA SCAR expression and cell proliferation in hRMVECs. Cell viability, levels of oxygen species (ROS), malondialdehyde (MDA) and adenosine triphosphate (ATP), as well as activities of antioxidant enzymes superoxide dismutase (SOD) and catalase (CAT) in the transfected hRMVECs in each group were detected using CCK-8 and their corresponding detection kits. Changes in mtDNA copy number in high-glucose-induced hRMVECs were observed by qRT-PCR. Additionally, western blot was applied to detect effect of overexpressing circRNA SCAR on the expression levels of mitochondrial function-related proteins (Drp1 and Fis1) and cell permeability-related proteins (claudin-5, occludin and ZO-1) in hRMVECs under high-glucose concentration. According to experimental results, high glucose significantly downregulated circRNA SCAR expression and inhibited cell proliferation in hRMVECs. Instead, overexpression of this circRNA SCAR promoted cell proliferation, reduced levels of ROS, MDA and ATP, and increased SOD and CAT activities in hRMVECs under high-glucose concentration. Also, circRNA SCAR overexpression reversed the high-glucose-induced decrease in mtDNA copy number as well as, high-glucose-induced upregulation of Drp1 and Fis1 protein expression and downregulation of claudin-5, occludin and ZO-1 protein expression in hRMVECs. In summary, circRNA SCAR promotes the proliferation of hRMVECs under high-glucose concentration, alleviates oxidative stress induced by high glucose, and improves mitochondrial function and permeability damage.
Keywords: retinal microvascular endothelial cells; high glucose; mitochondrial dysfunction; circRNA SCAR